Influenza D virus and host cell interactions during early stages of infection - Maina, Meshach (2024)
Influenza D virus (IDV) is the most recently identified member of the family Orthomyxoviridae. It is most closely related to ICV than other members of the family. Although it causes only mild respiratory disease, the virus is implicated in bovine respiratory disease complex (BRDC), which is a major cause of economic concern for cattle producers globally. Antibodies against IDV have been detected in humans and several animal spps, suggesting that IDV may have a broader host range than ICV. We therefore aimed to study the early interactions between IDV and host cells during infection to determine factors that influence IDV host range. Through this thesis, we determined the proteases involved in the activation of ICV and IDV, tested the hypothesis that the bovine turbinate (BT) cell line provides a useful in vitro model to study IDV viral–host interactions, determined the involvement of host entry restriction factors in IDV infection and the activation of the PI3K pathway. Overall, our findings shows that human airway trypsin-like protease (HAT) and its swine homologue (swAT) activates ICV and IDV pseudotypes with higher efficiency relative to TMPRSS2. RNA-Seq data demonstrated the involvement of genes related to type I or type III interferon responses in IDV infection of BT cells. Intrinsic innate immune responses including IFN-inducible transmembrane (IFITM) proteins restricted the entry of IAV, ICV and IDV pseudotyped viruses. Determination of the subcellular localization of bovine IFITM3 showed that it has an intracellular cytoplasmic distribution. KEGG pathway analysis of the transcriptomic data showed activation of the PI3K/Akt pathway. This led to the hypothesis that IDV activates the pathway in a similar way to influenza A virus (IAV), by non-structural NS1 protein binding the PI3K p85β subunit. However, pull-down and immunoprecipitation assays did not detect binding of IDV NS1 to p85β; this may be due to amino acid differences in the tyrosine-phosphorylated YXXXM motif that is important in the binding of the IAV NS1 to the p85β subunit. This suggests a different mechanism in preventing apoptosis after IDV infection.